Cyber Counseling Services in Covid-19 Pandemic - Resti Okta Sari (Al-Isyrof: Jurnal Bimbingan Konseling Islam, 2021)
During in COVID-19 pandemic, counselors switched the face-to-face counseling process to online counseling or in terms of guidance and counseling, namely cyber counseling. The application of cyber counseling services can be the right solution when psychological problems require immediate resolution. This cyber counseling service can also be applied by education counselors. This research was conducted to determine the application of cyber counseling during the COVID-19 pandemic, as well as the counseling process and media used by counselors. The method used in this research a literature study. The results show that the cyber counseling process is almost the same as the face-to-face counseling process, but several things need to be considered, such as the preparation stage which includes the availability of supporting and adequate hardware and software. Furthermore, the media used by cyber counseling can be in the form of applications, websites, telephones, chat what apps and video conferencing, and other social media. The advantages of cyber counseling can be accessed anywhere and in an adjustable time, the counselor can reach a wider range of counselees. Counselees and counselors can carry out the counseling process when and where by mutual agreement, although in the counseling process it is sometimes without signs and physical the counselee is easier to express thoughts and feelings. The weakness is that the diagnosis is less accurate and the intervention is less effective because the instructions and directions are given are less specific and non-verbal information becomes difficult to provide. Keywords: Cyber Counseling, COVID-19 Pandemic.